HERMENEUTIKA POSTMODERN: Wacana Pembuka atas Hermeneutika Jacques Derrida - Simamora, Serpulus (UNIKA Santo Thomas, 2005)
Even though people are not aware of postmodern philosophy or way of thinking, the philosophy, however has penetrated and thrusted every day life and becomes trendy in our common discourse in our time. Its characteristics such as liberal thinking, freedom of expression, criticism on any kind of authority and normative and universal idea – as sharp criticism to modern philosophy and way of thinking – have attractted people in expressing their thoughts through any medium in their lives. One of the area touched by the philosophy is hermeneutics. Many questions arise: In what sense does the postmodernism criticise the modernism? What is the basic presupposition of the philosophy? Within the field of hermeneutics, what is the contribution of the philosophy to hermeneutics but at the same time the danger enveloved inside?